2008
DOI: 10.1177/1753465808088902
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide, systemic inflammation, and the spirometric response to inhaled fluticasone propionate in severe chronic obstructive pulmonary disease: A prospective study

Abstract: Background:A subset of patients with chronic obstructive pulmonary disease (COPD) may respond more favorably to inhaled corticosteroids (ICS), but no simple method is currently utilized to predict the presence or absence of ICS responses in patients with COPD. We evaluated the ability of exhaled nitric oxide (F E NO) and serum inflammatory markers (C-reactive protein [CRP], interleukin-6 [IL-6], and interleukin-8 ) to independently predict spirometric responses to ICS in patients with COPD. Methods: Among 60 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 43 publications
4
35
1
Order By: Relevance
“…Antus et al reported that in 58 COPD patients with acute exacerbation, patients with increased FeNO at the time of exacerbation responded better to treatment with corticosteroids and bronchodilators 15. Similarly, after 4 weeks of treatment with ICS in a study of 60 ex-smokers with severe COPD, ICS responders had significantly higher baseline FeNO levels compared with non-responders 16. Akamatsu et al studied 14 patients with COPD and found that FeNO >35 ppb and evidence of atopy predicted improvement in FEV 1 with ICS/LABA when added to tiotropium 17.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Antus et al reported that in 58 COPD patients with acute exacerbation, patients with increased FeNO at the time of exacerbation responded better to treatment with corticosteroids and bronchodilators 15. Similarly, after 4 weeks of treatment with ICS in a study of 60 ex-smokers with severe COPD, ICS responders had significantly higher baseline FeNO levels compared with non-responders 16. Akamatsu et al studied 14 patients with COPD and found that FeNO >35 ppb and evidence of atopy predicted improvement in FEV 1 with ICS/LABA when added to tiotropium 17.…”
Section: Discussionmentioning
confidence: 97%
“…A reduction in eosinophilic airway inflammation has also been shown to reduce the number of future COPD exacerbations 2. Other investigators have determined that FeNO levels may be predictive of greater treatment response to corticosteroids and bronchodilator therapy 15,16. Antus et al reported that in 58 COPD patients with acute exacerbation, patients with increased FeNO at the time of exacerbation responded better to treatment with corticosteroids and bronchodilators 15.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, FeNO is regarded as the most promising indicator 39. Some studies have reported that patients with high FeNO levels will have a good response to corticosteroids and greater improvement in FEV 1 39,40. The reason for this result may be due to the fact that the FeNO level correlated well with the eosinophils, which is a good predictor for the response to corticosteroids 41,42.…”
Section: Methodsmentioning
confidence: 99%
“…[79] FENO may have a role in the monitoring of anti-inflammatory therapy of COPD and can be used to identify patients who may respond to steroids. Clearly, further studies are needed in this area.…”
Section: Clinical Application Of Fenomentioning
confidence: 99%